Caregiver’s Contacts: How to Get the Help You Need - Carolyn S. Wilken (EDIS)
FCS2258, a 2-page fact sheet by Carolyn Wilken, is the second in a series on caregiving and aging. This helpful worksheet contains a list of prompts for questions to ask and information to give when attempting to locate help or information about elder care. Published by the UF Department of Family, Youth and Community Sciences, November 2006.